Pesticide Safety Miniposter: Daily Personal Care: ENY-917/IN956, 8/2012 - Baldwin, Rebecca W.; Hill, Stephanie K.; Koehler, Philip; Walker, W.; Medley, J. C. (EDIS, 2012)
Anyone applying pesticides should be aware of the importance of preventing pesticide exposure to themselves, their families, and their pets by following a few personal care procedures each day. The information and video links (QR codes) on the Daily Personal Care poster provide technicians with examples of areas that are commonly contaminated by pesticides. The poster explains methods for the decontamination of vehicles, application equipment, personal items like cell phones, and clothing. Designed by R.W. Baldwin, S.K. Hill, Philip Koehler, W. Walker, and J.C. Medley, and published by the UF Department of Entomology and Nematology, August 2012. ENY-917/IN956: Pesticide Safety Miniposter: Daily Personal Care (ufl.edu)